PERANCANGAN PROGRAM LOYALITAS PELANGGAN DENGAN METODOLOGI WATERFALL UNTUK MENINGKATKAN LAYANAN PADA KING LAUNDRY (CKI ON SPOT, 2018)
ABSTRACT Maintaining old customers is more difficult than getting new customers because now information can be accessed online and easily. This makes buyers have many choices to try similar products with other brands or stay on one brand. Competition in the laundry business in residential areas is increasingly widespread, so many laundry businesses are losing customers with various reasons. Building a customer loyalty program at the laundry business is intended to keep customers from moving elsewhere. There are two main objectives of the customer loyalty pro8gram, the first is to increase sales revenue by increasing the level of purchases. The second goal is to build closer ties between brands and customers. The loyalty program developed aims to provide certain prizes based on the number of points collected by the customer. Points are collected based on the quantity of items you want to wash, calculated per kilogram. Points become a measure of customer loyalty as well as a benefit for customers. This system is an effort to improve the services of King’s Laundry.Keywords:   Customer loyalty, loyalty point, reward programs